Legal Analysis of Notary Deals Buy & Sale Binding Agreement (PPJB) - N. Dewi Ratnasari; Akhmad Khisni; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this study is to analyze and explain the legal analysis of the notarial deed of sale and purchase agreement (PPJB). To analyze and explain legal protection for the fulfillment of the rights of the parties if one of the parties defaults in the sale and purchase binding agreement (PPJB).The method used by the researcher is Empirical Jurisdiction and The specifications in this study are descriptive. Based on the results of the study that Legal analysis of the notarial deed of sale and purchase binding agreement (PPJB), namely this sale and purchase binding agreement deed does not provide legal certainty and protection to the parties regarding the agreement they made. The position of the Deed of Sale and Purchase Agreement is null and void due to the non-fulfillment of the legal requirements of an agreement. This sale and purchase agreement is carried out on the basis of an agreement even though the buyer knows that the object of the sale is a guarantee for the seller's debt to the bank.